SISTEM KONTROL MESIN FUSED DEPOSITION MODELLING - Cristian Awi; Gatot Soeharsono; Didi Widya Utama (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Fused deposition modeling is a rapid prototyping process that is very popular. Fused deposition modeling is actually one method of Three -dimensional printing. Fused deposition modeling process , namely by heating the thermoplastic material and then do the printing . Our focus is to learn, the engine control system fused deposition modeling with software arduino 1.6.8 with firmware marlin and other software 3d printer. experimental control system is done by testing the direction of motion and measuring the distance and then test the form . Making fused deposition modeling is intended as a prototype in order to understand the control system and how to innovate in the development of fused deposition modeling. The results of the control system in the form of a fused depositon modeling engine capable of running as expected and can create a physical model.